Models of economic growth - Mirrlees, James A.; Stern, N.H. (London : Macmillan, 1973)
This book is about growth theory,, the capital output ratio as well as labor share of output.
Proceedings of a Conference held by the International Economic Association at Jerusalem.
Include index.
oo 17/08/2018
Loans
Keywords: Economic development--Mathematical models